Rare case of an adult granulosa cell tumor in a young girl: A case report - Soe, Lwin; Bong, Andy Cheong Shin; Dayang Nurul Afifah, Sharkawi; Abigail Rembui, Jerip; Sunil, Munisamy; Tin, Moe Nwe (Obstetrical & gynaecological Society of Malaysia, 2022)
Introduction: Ovarian granulosa cell tumors are rare gynaecological cancer that arises from the sex-cord stromal cells of the ovary and represents 2% to 3% of all ovarian cancer. The adult type is the most common type and usually occurs during the perimenopausal period while the juvenile type mostly affects young women. Case Description: A 29-year-old woman, sexually naïve, presented with a four-month history of progressive abdominal distension associated with reduced effort tolerance and orthopnea for one week. She had a history of irregular menstruation since 18 years of age. Physical examination revealed a grossly distended abdomen without tenderness. The Computed Tomography of the Thorax, Abdomen, and Pelvis reported a large cystic mass occupying the whole entire abdomen and false pelvis measuring 22.3 x 30.8 x 35.2 cm in size, likely arising from the right ovary. The left Fallopian tube and ovary were normal with free fluid seen within the pelvis and right iliac fossa. During exploratory laparotomy, there was 50 cc of turbid straw-colored ascites fluid with 30 x 30 cm right ovarian cyst. Right salpingo-oophorectomy was done. The histopathological examination reported an adult granulosa cell tumor of the right ovary. Discussion: Most adult granulosa cell tumors (AGCT) follow a benign course and surgery is the primary treatment. Stage 1is the most common presentation and surgery is mostly curative as in this case. A female patient presenting with irregular menstruation and progressive distension of the abdomen should raise suspicion about the possibility of AGCT and needs immediate surgical treatment.